Assessing organisational development in primary medical care using a group based assessment: the Maturity Matrix™. Issue 4 (2nd August 2004) - Elwyn, G; Rhydderch, M; Edwards, A; Hutchings, H; Marshall, M; Myres, P; Grol, R
Abstract : Objective: To design and develop an instrument to assess the degree of organisational development achieved in primary medical care organisations. Design: An iterative development, feasibility and validation study of an organisational assessment instrument. Setting: Primary medical care organisations. Participants: Primary care teams and external facilitators. Main outcome measures: Responses to an evaluation questionnaire, qualitative process feedback, hypothesis testing, and quantitative psychometric analysis (face and construct validity) of the results of a Maturity Matrix™ assessment in 55 primary medical care organisations. Results: Evaluations by 390 participants revealed high face validity with respect to its usefulness as a review and planning tool at the practice level. Feedback from facilitators suggests that it helped practices to prioritise their organisational development. With respect to construct validity, there was some support for the hypothesis that training and non-training status affected the degree and pattern of organisational development. The size of the organisation did not have a significant impact on the degree of organisational development. Conclusion: This practice based facilitated group evaluation method was found to be both useful and enjoyable by the participating organisations. Psychometric validation revealed high face validity. Further developments are in place to ensure acceptability for summative work (benchmarking) and formative feedback processes (quality improvement).